1997
DOI: 10.1177/026361749701500703
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Water and other Polar Substances with Hydrophilic Centres on the Surface of Hydrophobic Adsorbents

Abstract: The adsorption of water and other polar substances on to the surface of graphitized carbon black and macroporous silica modified by polymethylhydride silicone has been studied using gas chromatography. The adsorption heat values of the substances studied were determined and the concentration of surface hydrophilic centres estimated. Conclusions have been drawn concerning the number of water molecules adsorbed on to hydrophilic centres at low surface occupation values. In the case of water adsorption on the gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…An extremely important prerequisite to the studies of the interaction of water and methanol with carbon materials is the thermal pre-processing of the samples (Vartapetyan and Voloshchuk, 1995;Tarasevich et al, 1998;Kiselev and Yashin, 1967). In our experiments it was shown that pre-processing of the GTCB at 200 • C resulted in the fact that no elution peaks were observed after the injection of first few portions of water into the column packed with the adsorbent, which indicates that at the initial stage the water molecules are chemisorbed by the sorbent.…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…An extremely important prerequisite to the studies of the interaction of water and methanol with carbon materials is the thermal pre-processing of the samples (Vartapetyan and Voloshchuk, 1995;Tarasevich et al, 1998;Kiselev and Yashin, 1967). In our experiments it was shown that pre-processing of the GTCB at 200 • C resulted in the fact that no elution peaks were observed after the injection of first few portions of water into the column packed with the adsorbent, which indicates that at the initial stage the water molecules are chemisorbed by the sorbent.…”
Section: Methodsmentioning
confidence: 67%
“…Initial sections of water and methanol vapour adsorption isotherms obtained by the gas-chromatographic method at the GTCB surface were found to be convex with respect to the pressure axis for all temperatures, while for the TEG the isotherms were convex to this axis at 52 and 62 • C. This latter fact should be ascribed to the interaction of polar molecules of the studied substances with active hydrophilic centres that exist at the surfaces of the adsorbents (Vartapetyan and Voloshchuk, 1995;Tarasevich, 2001a;Tarasevich et al, 1998). The adsorption isotherms of water and methanol vapours on the GTCB sample are shown in Figs.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, at liquefaction, the heat is lower, even though there are about 4 hydrogen bonds around each water molecule, because repulsive forces also contribute to the energy of a cluster. Quantum mechanical calculations of the heat at zero loading, for water on an OH graphite, give values in the range -15 to -26 kJ mol -1 [38][39][40].…”
Section: The Average Surface Excess Was Calculated Frommentioning
confidence: 99%
“…Recently, a notable development has been the use of computer simulation studies. All the molecular simulation were realized on the basis of the Dubinin−Serpinsky concept of primary adsorption sites and the island mechanism of water adsorption. , Obviously, the simulation results show that the adsorption of water occurs via the formation of three-dimensional clusters centered on oxygenated sites. Despite these interesting results, as pointed out by Kaneko, because the contribution of the dispersion force to the whole intermolecular interaction of water is only 24% and the intermolecular interaction cannot be described by the Lennard-Jones potential, it is not easy to simulate the molecular state of water in carbon micropores, and therefore, further experimental analysis is required. Important experimental contributions in this analysis, realized by Iiyama et al, are the in situ X-ray diffraction and small-angle X-ray scattering studies of water confined in carbon micropores.…”
Section: Introductionmentioning
confidence: 99%